Daya Tarik Media Digital Sebagai Media Dakwah Untuk Generasi Milenial - Reza Mardiana (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
Technological developments of this era affected the da’wa model as never beforerapidly and dynamic. One of the technological trends of this millenium is digital media because it is faster and easer to acces information. Da’wa is to call, invite, and encourage someone to do a good thing. Da’wa should utilities any available communication instrument. If not, then da’wa would be falling behind and slowing down so that is would affect morals and morals in the millennials. This article discussing digital media whether it can be the appeal of millenials in preaching. By approach to literature studies that later date are elaborately analyzed, the data could explain that a climb through digital as by using social media asa trendy and fahionable medium of communication can become an attraction for millenials to preach. This is due to the large number of people who use social media as mesia in efforts to deliver the message of the da’wa. Keywords: da’wa media; digital da’wa; millenials.